Knowledge and Self-Care Practice on Hypertension among Hypertensive Patients in a Tertiary Level Hospital of Kathmandu - Satyal, Geeta K; Rai, Lalita; Gautam, Roshani; Dangol, Bhuvan K; Shakya, Rajina (Journal of Institute of Medicine Nepal, 2020)
Introduction Hypertension is a public health challenge and major risk factor for cardiovascular disease in the developing as well as developed countries. The successful management of hypertension depends upon patient’s knowledge on hypertension and self-care practices.MethodsA descriptive cross-sectional study was conducted to identify the knowledge and self-care practice on hypertension among 212 hypertensive patients attending in outpatient department of Manmohan Cardiothoracic Vascular and Transplant Center (MCVTC). Non-probability purposive sampling technique was used. Data was collected through face-to-face interview by using structured questionnaire. Data was analyzed using SPSS version 16.0.ResultsThis study showed that 57.5% of the respondents had adequate level of knowledge on hypertension and 57.1% of the respondents had good overall self-care practice. Regarding self-care practice, we found 100% medicine adherence, 85.8% respondents avoided alcohol and 84.9% avoided smoking, 50.9% followed weight management practice, 48.6% followed dietary management and 44.8% performed physical activity. Level of knowledge was significantly associated with age, gender, educational status and occupation. Self-care practice was only significantly associated with educational status. Level of knowledge and self-care practice were significantly positively correlated.ConclusionMore than half of the respondents had adequate level of knowledge. Regarding self-care practice, nearly sixty percent of the respondents had good self-care practice. To bring those rates to higher level, awareness programs should be launched about diseases and self-care practice on hypertension.